Analysis of Physical Components of the Ability to Kick the Ball Into the Goal in the SSB Kalegowa Soccer Game - Achmad Karim (CV Lentera Cendekia Indonesia, 2026)
This study aims to determine 1) the relationship between leg muscle strength and the ability to kick the ball into the goal in the SSB Kalegowa soccer game. 2) the relationship between ankle coordination and the ability to kick the ball into the goal in the SSB Kalegowa soccer game. 3) the relationship between balance and the ability to kick the ball into the goal in the SSB Kalegowa soccer game. 4) the relationship between leg muscle strength, ankle coordination and balance together with the ability to kick the ball into the goal in the SSB Kalegowa soccer game. The sample used was SSB Kalegowa as many as 30 people, taken using random sampling technique. Data analysis techniques used in this study were descriptive analysis, correlation analysis, and regression analysis at a significant level (α) = 0.05. The results of this study indicate that: 1) there is a significant relationship between leg muscle strength and the ability to kick the ball into the goal in the soccer game by obtaining a correlation coefficient value (r) = 0.800 with a probability level (0.000) <0.05; 2) There is a significant relationship between foot-ankle coordination and the ability to kick the ball into the goal in soccer, with a correlation coefficient (r) of 0.768 with a probability level of (0.000) <0.05; 3) There is a significant relationship between balance and the ability to kick the ball into the goal in soccer, with a correlation coefficient (r) of 0.741 with a probability level of (0.000) <0.05; 4) There is a significant relationship between leg muscle strength, foot-ankle coordination, and balance together with the ability to kick the ball into the goal in soccer, with a coefficient of determination (r2) of 0.775 or 77.5%.